Duplicated RCA with Anomalous Origin of Left Circumflex Artery: A Rare Case Report - Pawan Kumar Garg (Journal of Clinical and Diagnostic Research, 2018)
Coronary artery anomalies are found in around 1-2% of patients undergoing coronary angiography. Uncovering of more coronary anomalies has increased with increase in awareness and easy availability of non invasive Computed Tomography Coronary Angiography (CTCA). We present a rare case of a 64-year-old female with a history of atypical chest pain and mild ST depression ECG changes who underwent CTCA. The present case revealed unusual findings of an anomalous origin of the Left Circumflex Coronary artery (LCx) from the proximal Right Coronary Artery (RCA) with duplicated right coronary artery after arising as a common trunk from right coronary cusp. In the present case report we attempted to highlight the rarity of this coronary anomaly.